Torque response characteristics of a controllable electromagnetic damper for seat suspension vibration control. (1st November 2019) - Liu, Pengfei; Xia, Xiangjun; Zhang, Nong; Ning, Donghong; Zheng, Minyi
Highlights: A novel method to switch resistance is proposed to change the resistance in the circuit of the electromagnetic damper system. The response time and dynamic tracking performance of the electromagnetic damper system are investigated. A sliding mode controller is designed for the electromagnetic damper seat suspension. Abstract: In this paper, a novel resistance switching method is proposed to control an electromagnetic damper (EMD) system of a vehicle seat suspension, and torque response characteristics of the EMD system are investigated in detail. First, the relationship between electromagnetic torque and circuit resistance of the EMD system is established. The basic parameters of the EMD system are identified by least squares fitting, and the resistance distribution is optimized to meet the demand damping of seat suspension. Second, the electromagnetic torque response time and the continuously dynamic torque tracking performance of the EMD system are investigated experimentally. The time required for the torque change from its initial to 80% of the final state and the final state is measured, respectively. The results show that the response time required for torque decrease is shorter than the response time required for torque increase; the EMD system has excellent torque response and torque tracking performance and is suitable for seat suspension vibration control. Finally, two typical vehicle body vibration excitations are exerted on the EMD seat suspension. The test results verify that the EMD seat suspension has excellent controllable damping and can significantly isolate the vibration of driver body when applying a sliding mode control method.